Tough and dense boron carbide obtained by high-pressure (300 MPa) and low-temperature (1600°C) spark plasma sintering - Badica, Petre (2014)
Dense boron carbide (above 95%) was achieved through high pressure (300 MPa) and low temperature (1600°C) Spark Plasma Sintering (SPS). This approach resulted in improvement of fracture toughness and of dynamic toughness when compared to corresponding toughness values of the sample sintered by conventional SPS (2100°C, 50 MPa). Dynamic toughness was extracted from Split Hopkinson Pressure Bar measurements. Results are understood based on microstructure and on very different behaviour of the samples in respect to residual B2O3 and carbon available in the raw B4C powder.